Manufacturing of regular microstructures by methods of LIGA - Technologies - Аumalikova М. N.; Timchenko N. A. Nikolay Alekseevich; Kuznetsov S. I. Sergey Ivanovich; Goldenberg B. G.; Pindurin V. F.; Litvin S. V.; Kanaev V. G. (2012, 2012)
Title screen